Determinants and Consequences of Information Exchange Quality in the Buyer-Supplier Relationship: Evidence from the Fishing Industry of Tanzania - Singogo , Patrick Christopher; Kassimba , Yasinta Amani (University of Dar es Salaam Library Journal, 2024)
Given a number of studies that recognise the imperative of information exchange in buyer-supplier relationships, there is still a gap to fill. Thus, this study investigated the determinants and consequences of information exchange quality in the buyer-supplier relationships of the fishing industry in Tanzania. Specifically, the study aimed to investigate the associations that exist between information exchange willingness and information exchange quality, information exchange content and information exchange quality, information exchange quality, and perceived information exchange benefits. Transaction Cost Economics (TCE) theory and empirical literature guided the development of hypotheses. The study employed a cross-sectional research design with a quantitative approach, and a structured questionnaire was used as the main instrument for data collection. The study used partial least square structural equation modelling (PLS-SEM) aided by SmartPLS 3.3 to validate the measurement model and test the hypotheses by using data from 300 fish purchasing managers from the Mwanza and Dar es Salaam regions. Findings indicate that information exchange willingness and content are positively and significantly associated with information exchange quality. Furthermore, findings indicate that information exchange quality is positively and significantly associated with perceived information exchange benefits. This study contributed to the imperative of information exchange quality in the dynamic supply chain for the growth of the fishery industry in Tanzania, as it offers significant meaning to fish purchasing practitioners and policymakers. Moreover, the findings have implications for transaction cost economics theory by further considering the quality of information exchange rather than information exchange in general.